A FEASIBILITY STUDY ON HELIUM ISOTOPES IN ICE CORE - サノ, ユウジ; トウジマ, ヤスノリ; ワキタ, ヒロシ; マキデ, ヨシヒロ; トミナガ, タケシ; フジイ, ヨシユキ; SANO, Yuji; TOHJIMA, Yasunori; WAKITA, Hiroshi; MAKIDE, Yoshihiro; TOMINAGA, Takeshi; FUJII, Yoshiyuki (National Institute of Polar Research, 1992)
P(論文) The isotope ratio of atmospheric helium, ^3He/^4He ratio, is believed to be constant on a global scale since the mixing time for the atmosphere is significantly shorter than the residence time for helium. Human activity such as fossil fuel exploitation may release significant amounts of crustal helium with low ^3He/^4He ratio. Recently a decrease in the atmospheric ^3He/^4He ratio from 1.362×(10)^<-6> in December 1977 to 1.339×(10)^<-6> in September 1988 was reported. These observations are compatible with an estimate of the anthropogenic release of crustal helium. For verification of the ^3He/^4He change with time, measurement of ancient air before the industrialization is highly desirable. Air bubbles in Antarctic ice cores may be the most suitable samples for the purpose. The ice core samples, which were obtained at Mizuho Station in 1984,were carefully processed to extract the trapped air at the National Institute of Polar Research. A released air sample of about 0.3ccSTP from ice cores at 330-m depth, which was estimated to be about 3600 years old, was introduced into an evacuated stainless-steel canister equipped with a stainless-steel bellows valve. The ^3He/^4He and ^4He/^<20>He ratios of the samples were measured using the purification vacuum line and high precision mass spectrometer at the University of Tokyo. The observed ^3He/^4He ratio relative to the running standard was converted into the absolute ^3He/^4He ratio using a calibration line based on artificially mixed in-house standard gases. The observed ^4He/^<20>Ne ratio was calibrated against the present air standard. Experimental errors of ^3He/^4He and ^4He/^<20>Ne ratios are about 1% and 10%, respectively. Chemical compositions of the samples were determined using a quadrupole mass spectrometer. The ^3He/^4He and ^4He/^<20>Ne ratios of air bubbles extracted from ice core samples before industrial activity vary significantly from 9.9×(10)^<-7> to 1.30×(10)^<-6> and from 0.31 to ...